Morphological and genetic relationships among snakehead Channa striata (Bloch, 1793) populations in Peninsular Malaysia - Abdul Rahim, Mohammad Hafiz (2012)
Haruan, the local name for the snakehead Channa striata, is a tropical freshwater fish from the Channidae family that is valuable in terms of importance in economics, i.e. as food, and in medicine. Thus, this study was undertaken to determine morphological and genetic relationships among 6 populations of C. striata in Peninsular Malaysia. The morphological and genetic variation of C. striata was studied based on polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) of the mitochondrial DNA cytochrome b gene (mtDNA cyt b) and morphometric and meristic analysis of samples collected from 6 C. striata locations around Peninsular Malaysia, namely Johor, Kedah, Kelantan, Pahang, Perak, and Terengganu. A total 120 specimens were used, with standard lengths ranging 17.50–37.50 cm, total lengths ranging 20.60–44.10 cm, and weights ranging 76.70–675.00 g.Five meristic counts and 23 morphometric measurements were used for the morphological analysis. The quantitative data were analysed by univariate analysis of variance (ANOVA) and multivariate analysis of discriminant function analysis (DFA). The morphometric characteristics were more adequate than the meristic characters for good separation of the populations. In DFA, the results indicated that C. striata from different populations can be distinguished using several morphometric characters, namely the ratios of dorsal fin height to standard length (DFH/SL) and caudal peduncle height to standard length (CPH/SL). The findings for the morphological analysis refute an earlier hypothesis of there being no morphological variation between populations of C. striata. For C. striata population genetics, 5 restriction endonucleases yielded enzyme-specific restriction morphs in a total of 29 composite mitochondrial DNA (mtDNA) haplotypes. The pairwise ФST statistics (-0.01861 to 0.60629) and analysis of molecular variance (AMOVA) (37.57%), results indicated consistency, with sufficient information existing to construct a rational explanation of the snakeheads‟ genetic heterogeneity. This support for the findings showed that the C. striata populations were separated into 2 major clusters, namely clade I (containing the Johor population) and clade II (a mixture of the Kedah, Kelantan, Pahang, Perak, and Terengganu populations), based on unweighted pair group method with arithmetic mean (UPGMA) cluster analysis and the haplotype network of mtDNA cyt b. The patterns of high levels of haplotype diversity (h = 0.6789–0.8737) and moderate nucleotide diversity (π = 0.008–0.0181), the observed star or dumbbell-shaped structure of the haplotype network, neutrality tests (D = -0.76304 to 0.53277, P > 0.05 and Fs = -6.16223 to -2.97325, P < 0.05), and mismatch distribution (bimodal or unimodal) tests demonstrated that whole populations of C. striata saw a recent population demographic expansion. The estimated population expansion in the mtDNA cyt b of C. striata populations occurred 1.41–1.69 million years ago. However, based on the net Tamura and Nei genetic distance, the divergence among regional populations occurred 0.72–2.6 million years ago. These findings suggest that morphological and genetic studies provide the information required for increasing the efficiency of C. striata management in Peninsular Malaysia, which will be helpful in fisheries, and to biologists, and taxonomists studying these fascinating fishes.